Investigating readiness to use Internet and mobile services of diabetic patients of a middle-income country - Jafari,Javad Javad; Karimi Moonaghi,Hossein; Ahmady,Soleiman; Zary,Nabil; Masiello,Italo (PeerJ PrePrints, 2015)
Background: Diabetes mellitus is increasing worldwide, especially in developing countries, as a consequence of urbanization. The use of the Internet and mobile service are increasing as well. The independent use of the Internet and mobile technologies by the patients could be a key step towards self-care management of the disease. Methods: A validated questionnaire with two parts was used and was completed by patients who came to two diabetic clinics for routine checkup. The first part consisted of 16 items collecting demographics information. The second part contained 26 items about the specific use of the Internet and mobile services to access information. Results: 407 questionnaires were completed. 108 (26,5 %) had routine access to Internet, of which 95,4 % had routine access to mobile services and 77,8 % were positive to the use of a Persian website for medical information. Yet, 55 % of respondents preferred to get information from TV, radio and educational courses. Conclusions: Data suggest that most diabetic patients who use the Internet in this study were willing to receive educational material by the Internet. However, many still prefer traditional means of information. Our future research is going to focus on early adopters.
Keywords: internet use; mobile services; diabetic patients; Iran; readiness